Cataract halos: A driving hazard in aging populations. Implication of the Halometer DG test for assessment of intraocular light scatter - Babizhayev, Mark A.; Minasyan, Hayk; Richer, Stuart P. (Applied ergonomics, 2009)
Cataract, regardless of etiology, results in light scatter and subjective glare. Senile cataract is emerging as a crucial factor in driving safely, particularly in night driving and adverse weather conditions. The authors examined this visual impairment using a new Halometer DG test in the eyes of older adult drivers with and without cataract. Examined subjects consisted of n = 65 older adults with cataract in one or both eyes and n = 72 adult drivers who did not have a cataract in either eye. Subjects were examined for distance high contrast visual acuity (VA) and red/green disability glare (DG) with a new halo generating instrument. Subjects also completed a subjective Driving Habits Questionnaire (DHQ), designed to obtain information about driving during the past year. DG increased with age of the driver. VA and Halometer DG testing of better and worse eyes prognosticated impairments which significantly affect driving performance. Cataract subjects demonstrated increased Halometer DG scores and were two to four times more likely to report difficulty with driving at night and with challenging driving situations than were cataract-free drivers. DG is a specific cataract-induced functional age-related risk factor of driving difficulty, easily measured by a technician with a new Halometer DG device. Optometrists and ophthalmologists should incorporate Halometer DG testing in their pre-examination vision testing rooms for patients over age 55, and also perform this test on others who complain about glare. Traffic safety engineers should incorporate automotive optical-microprocessor-aided tests for DG into cars, to alert drivers of mild functional impairments and progressive degrees of DG sensitization.